H alpha kinematics of a z similar to 1 disc galaxy from near-infrared integral field spectroscopy - Smith, J; Bunker, A; Vogt, N; Abraham, R; Aragon-Salamanca, A; Bower, R; Parry, I; Sharp, R; Swinbank, A (2004)
In this Letter we present the first 3D spectroscopic study of Hα emission in a z ∼ 1 field galaxy with an integral field unit. Using the Cambridge Infrared Panoramic Survey Spectrograph (CIRPASS) on Gemini-South, we map the spatial and velocity distribution of Hα emission in the z = 0.819 galaxy CFRS 22.1313. We detect two Hα emitting regions with a velocity separation of 220 ± 10 km s -1. Combining the 2D map of Hα emission with Hubble Space Telescope F814W imaging, we determine a lower limit of 180 ± 20 km s -1 for the rotation velocity of this M B(rest) ∼ -21 galaxy. We note that our value is significantly higher than the rotation velocity of 120 ± 10 km s -1 reported by Barden et al. for their long-slit spectroscopic study of this galaxy. Our lower limit on the rotation velocity is entirely consistent with no evolution of the rest B-band Tully-Fisher relation. The position of this galaxy relative to the mean rest B-band Tully-Fisher relation of Pierce and Tully is consistent with brightening of no more than ∼1 mag at z = 0.8. A larger integral field unit sample, without the uncertainties inherent to long-slit samples, is needed to determine the evolution of the Tully-Fisher relation accurately out to z ∼ 1.